Diversity of ectomycorrhizal fungal morphotypes and host-adaptation in contrasting populations of Pinus greggii var. australis (Pinaceae) - Rodríguez-Gómez-Tagle, Gabriela; Vargas Hernández, J. Jesús; López Upton, Javier; Pérez Moreno, Jesús (Instituto de Ecología, A.C., 2024)
Background and Aims: The compatibility between mycorrhizal fungi and trees is a consequence of coevolutionary processes in response to selection pressures. The diversity and differentiation of morphotypes from ectomycorrhizal fungi (ECM) communities in natural populations of Pinus greggii var. australis were analyzed in two contrasting environments (Zacualpan and Cieneguilla, Mexico), and in reciprocal combinations of seed and inoculum origin in the nursery.Methods: Soil samples were collected from two natural populations of P. greggii var. australis. A portion of the samples was used to obtain and identify mycorrhizal morphotypes, and the other was used as inoculum for the nursery bioassay. Shannon diversity index and Bray-Curtis similarity index were used to estimate diversity and differentiation degree of ECM communities in both natural populations and in seedlings from the nursery bioassay.Key results: Thirty-two different ECM morphotypes were found in the natural populations, 23 in Zacualpan, 17 in Cieneguilla, and eight in both of them. ECM morphotypes diversity was higher in Zacualpan, with a strong differentiation from the other community. At the beginning of the bioassay, Tomentella sp. was the dominant morphotype, but after eight months it was Rhizopogon sp. Cenoccocum geophilum and Wilcoxina sp. morphotypes were also identified. Root colonization dynamics was faster with the Cieneguilla origin for either guest or host. ECM diversity was higher in the sympatric associations at the beginning, but 12 months after sowing it was higher in the allopatric ones. Conclusions: A high diversity and strong differentiation in ECM morphotypes was found in two natural P. greggii var. australis populations. However, diversity and differentiation of the ECM community morphotypes in the bioassay decreased with age of seedlings, indicating an effect of the nursery environment in homogenizing the composition of the ECM community.